Seleksi Konsorsium Mikroorganisme untuk Pembenah Lumpur Sidoarjo sebagai Media Tanam - Pikoli, Megga Ratnasari; Setyawati, Adi Puji; Larasati, Tri Retno Dyah; Mulyana, Nana (Perhimpunan Biologi Indonesia, 2018)
ABSTRACTThe mud that erupted in Sidoarjo, East Java, has been known from several studies can be used as plant growth media. However, its ability has limitations, particularly due to the very high heavy metal content and phenol will gradually poison the plants. Therefore, a study has been conducted in order to obtain a consortium of microorganisms which have ability to support plants growth and remediate the mud so that further can be used as a growth media. The selected microorganisms consist of Azotobacter sp. KDB2, Bacillus sp. KLBN1, Bacillus sp. BMC4, Pseudomonas sp. BMC6, Trichoderma sp. PJF6 and Trichoderma sp. PJF7F7, which were combined in five consortia, namely K1, K2, K3, K4, and K5. The selection was performed on the ability to produce indole acetic acid, dissolve phosphate, decrease phenol concentration, and decrease the concentration of Pb and Cd ion metals. The results showed that the five consortia have capacity in the five parameters examined. The ability to remove Pb by microbial consortia which consist of Azotobacter, Bacillus, Pseudomonas, and Trichoderma is a new information of the role of microorganism on heavy metal removal. The existence of positive and negative interactions within each consortium lead to differences in the kind of superior consortium generated from each parameter. The consortium K4 showed advantages in 3 parameters, that were in the indole acetic acid production and the Pb and Cd decreases, while the other consortia showed the best capacity only on one of the parameter examined. Therefore, the selected consortium recommended for fixing the Sidoarjo mud is K4, which consists of Azotobacter sp., Bacillus sp. BMC4, Pseudomonas sp. BMC6, Trichoderma sp. PJF6 dan Trichoderma sp. PJF7.Keywords: biofertilizer, bioremediation, Azotobacter, Bacillus, Pseudomonas, Trichoderma